Analysis of Potentially Modifiable and Unmodifiable Risk Factors of Myocardial Infraction: Systematic Review - Abudaqa, Loai; Hegazi, Shady; Al-Swari, Nabil; Gharbi , Maro; Alyasseen, Osama; Lozon, Hadeel; Alaila, Farah; Al Nooryani, Arif (International Journal of Public Health Excellence (IJPHE), 2023)
Myocardial infarction is a leading cause of death, disability, and decreased productivity worldwide, particularly in relation to cardiovascular disease. The aim of this study was to assess the contribution of both modifiable and non-modifiable risk factors to the incidence of myocardial infarction in a large population (32,585 patients; 26,020 male and 6,564 female). An extensive search was conducted on databases such as PubMed, Google Scholar, Scopus, Medline, and Web of Science, limited to full-text articles written in English and published from 2015 onwards, using keywords such as "myocardial infarction (MI)," "epidemiology," and "risk factors." We conducted a thorough search of databases and screened articles using PRISMA guidelines. Six articles were found eligible for the study's objectives, the majority of the 32,585 subjects were males (79.8%) and aged between 61 to 70 years (59.5%). 20.4% of the subjects had a positive family history, race and ethnicity included white (32.3%), black (28.1%) and others (36.1%) and the most common modifiable risk factors were hypertension (48.9%), smoking (42.2%), hypercholesterolemia (40.9%), and diabetes (24.4%). The Mean BMI was 19.6 ranging from 25.0-39.9. Hypertension was significantly associated with gender, age, and diabetes, while hypercholesterolemia was positively associated with diabetes and hypertension. In the large population, myocardial infarction is prevalent in men and patients with hypertension. Modifiable and non-modifiable risk factors, along with coronary artery occlusion, increase with age, highlighting the importance of healthy lifestyle training and early control of modifiable risk factors to prevent cardiovascular diseases.